Effect of clinical factors on trajectory of functional performance in patients undergoing hemodialysis. Issue 1 (1st January 2021) - Chen, Jin-Bor; Li, Lung-Chih; Lee, Wen-Chin; Moi, Sin- Hua; Yang, Cheng-Hong
Abstract: Purpose: This study aimed to investigate the association between clinical factors and temporary changes in functional performance in patients undergoing hemodialysis. Methods: This was a retrospective, longitudinal observational study conducted from 2015 to 2017. Eight-two patients undergoing hemodialysis in the outpatient clinic were enrolled. Functional performance was measured using the Karnofsky Performance Status (KPS) scale. Collected data for analysis included demographics, laboratory parameters, and KPS scale scores. All participants were grouped into a high KPS cluster and a low KPS cluster based on dynamic changes in KPS scales from 2015 to 2017. Results: Participants in the high KPS cluster demonstrated an approximate trend, and those in the low KPS cluster demonstrated a low pattern. By stepwise selection model analysis, age (OR 1.12, 95% CI 1.03–1.23, p  = 0.011), serum BUN (OR 1.08, 95% CI 1.02–1.16, p  = 0.015), calcium levels (OR 3.24, 95% CI 1.2–8.73, p  = 0.02), and beta-2-microglobulin (OR > 1.0, CI >1.00-<1.01, p  = 0.031) showed risk for the low KPS cluster. Male sex (OR 0.20, 95% CI 0.04–0.96, p  = 0.045) and albumin level (OR 0.02, 95% CI 0–0.4, p  = 0.009) showed a low risk for the low KPS cluster. Conclusions: A different trajectory pattern was observed between the high and low KPS clusters in a 3-year period. Risk factors for the low KPS cluster were age, serum BUN, calcium, and beta-2-microglobulin levels. Male sex and serum albumin levels reduced the risk for the low KPS cluster.